Pengaruh Kualitas Laporan Keuangan, Debt Maturity, dan Kinerja Profitabilitas Terhadap Efisiensi Investasi - Marsya, Monica; Dewi, Rosiyana (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2022)
This study aims to prove that the quality of financial statements, debt maturity, and profitability performance can affect investment efficiency. Quality financial reports and good financial performance can maintain the company's financial stability so as to increase the level of investment efficiency. This study tested the multiple regression model, using the SPSS tool. The population in this study are manufacturing companies listed on the 2018-2020 BEI which were selected by purposive sampling so that the total sample was 104 data. The results of this study prove that debt maturity and profitability performance have a positive effect on investment efficiency, but the quality of financial reports does not affect investment efficiency and debt maturity does not moderate the effect of financial statement quality on investment efficiency. The results of this study have implications for both theory and practice, for companies and the government should strive to improve the quality and performance of financial reports to increase investor confidence.